Unveiling the Potential of Nanoclays in Pharmaceuticals - Rabab Kamel; Giuseppina Nocca; Elena Mazzinelli; Somaia S. Abd El-Karim; Valerio Papa; Ilaria Cacciotti; Nermeen A. Elkasabgy (AAPS PharmSciTech, 2025)
Clay minerals or nanoclays are layered aluminosilicate nanoparticles with unique physicochemical properties, excellent biocompatibility, high surface area, lamellar structure, diverse ion-exchange capacity, tuneable surface chemistry enabling them to form different intermolecular interactions which offer supreme prospects for optimized pharmaceutical applications. This review article dives into the key characteristics of different types of nanoclays like Halloysite, Kaolinite, Sepiolite, Montmorillonite, Bentonite and Laponite, highlighting their possible exploitation within the pharmaceutical landscape. Also, the review describes the recent advances in nanoclay-based drug delivery systems and discusses the role of nanoclays as drug carriers and their use in tissue engineering and gene therapy. Nanoclays, are used to modulate drug release and stabilize the loaded active molecules as well as to enhance drug loading. Interdisciplinary research, advanced characterization techniques, and careful formulation designs are required to augment the use of nanoclays in various pharmaceutical applications. Despite the faced challenges, research on nanoclay-based drug delivery systems is growing. With targeted research and development, nanoclays are poised to redefine the biomedical domain, offering tailored and efficient therapies for a multitude of diseases. Graphical Abstract

Phytosterol-enriched Camellia oleifera Abel seed oil obtained by subcritical butane extraction: Physicochemical properties and oxidative stability - Tao Yang; Rui He; Qiuyu Xia; Ilaria Cacciotti; Sameh A. Korma; Weimin Zhang; Guohui Yi (Food Chemistry, 2025)

Exploration of underutilized chayote fractions following drying and extraction - Ashiq Hussain; Faiza Iftikhar Gorsi; Muhammad Qasim Ali; Shazia Yaqub; Afifa Asif; Barira Bibi; Farooq Arshad; Ilaria Cacciotti; Sameh A. Korma (Food Chemistry, 2025)

The CRZ1 transcription factor in plant fungi: regulation mechanism and impact on pathogenesis - A. Cacciotti; M. Beccaccioli; M. Reverberi (Molecular Biology Reports, 2024)
Calcium (Ca 2+ ) is a universal signaling molecule that is tightly regulated, and a fleeting elevation in cytosolic concentration triggers a signal cascade within the cell, which is crucial for several processes such as growth, tolerance to stress conditions, and virulence in fungi. The link between calcium and calcium-dependent gene regulation in cells relies on the transcription factor Calcineurin-Responsive Zinc finger 1 (CRZ1). The direct regulation of approximately 300 genes in different stress pathways makes it a hot topic in host-pathogen interactions. Notably, CRZ1 can modulate several pathways and orchestrate cellular responses to different types of environmental insults such as osmotic stress, oxidative stress, and membrane disruptors. It is our belief that CRZ1 provides the means for tightly modulating and synchronizing several pathways allowing pathogenic fungi to install into the apoplast and eventually penetrate plant cells (i.e., ROS, antimicrobials, and quick pH variation). This review discusses the structure, function, regulation of CRZ1 in fungal physiology and its role in plant pathogen virulence.

Intrinsic properties and extrinsic factors of food matrix system affecting the effectiveness of essential oils in foods: a comprehensive review - Liyou Zheng; Hongyan Guo; Miaomiao Zhu; Liangliang Xie; Jun Jin; Sameh A. Korma; Qingzhe Jin; Xingguo Wang; Ilaria Cacciotti (Critical Reviews in Food Science and Nutrition, 2024)

Effect of co-fermentation system with isolated new yeasts on soymilk: microbiological, physicochemical, rheological, aromatic, and sensory characterizations - Sameh A. Korma; Li Li; Mohamed Ghamry; Qiyang Zhou; Peipei An; Khaled A. E. Abdrabo; Muhammad Faisal Manzoor; Abdur Rehman; Sobia Niazi; Ilaria Cacciotti (Brazilian Journal of Microbiology, 2022)